Study protocol: BRInging the Diabetes prevention program to GEriatric Populations - Beasley, Jeannette M.; Johnston, Emily A.; Sevick, Mary Ann; Jay, Melanie; Rogers, Erin S.; Zhong, Hua; Zabar, Sondra; Goldberg, Eric; Chodosh, Joshua (Frontiers in Medicine, 2023)
In the Diabetes Prevention Program (DPP) randomized, controlled clinical trial, participants who were ≥60 years of age in the intensive lifestyle (diet and physical activity) intervention had a 71% reduction in incident diabetes over the 3-year initial trial. However, few of the 26.4 million American adults age ≥65 years with prediabetes are participating in the National DPP. The BRInging the Diabetes prevention program to GEriatric populations (BRIDGE) randomized trial compares an in-person DPP program Tailored for Older AdulTs (DPP-TOAT) to a DPP-TOAT delivered via group virtual sessions (V-DPP-TOAT) in a randomized, controlled trial design (N=230). Eligible patients are recruited through electronic health records (EHRs) and randomized to the DPP-TOAT or V-DPP-TOAT arm. The primary effectiveness outcome is 6-month weight loss and the primary implementation outcome is intervention session attendance with a non-inferiority design. We are using a pragmatic approach in order to inform future studies conducted in other settings. Findings will inform best practices in the delivery of an evidence-based intervention that could reach a larger proportion of adults aged 65 and over with prediabetes.